2020
DOI: 10.1186/s12864-020-6601-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of CNGC genes in Chinese jujube (Ziziphus jujuba Mill.) and ZjCNGC2 mediated signalling cascades in response to cold stress

Abstract: Backgrounds: Cyclic nucleotide gated channels (CNGCs) play multifaceted roles in plant physiological processes, especially with respect to signalling processes, plant development, and responses to environmental stresses. However, little information is known about the CNGC family in the large cosmopolitan family Rhamnaceae, which has strong tolerance to biotic and abiotic stresses. Results: In the current study, a total of 15 ZjCNGCs which located on 7 chromosomes were firstly identified in Chinese jujube (Zizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…For the cold treatment, calli at same growth stage and condition were transferred at 4 °C and then collected within 0, 1, 6, 12, 24, and 48 h. Calli incubated at 25 °C were collected and used as negative controls [ 26 ]. For the salinity treatment, callus tissues were subjected to a 150 mM NaCl and NaHCO 3 -NaOH solution (pH 9.5) for 0, 1, 6, 12, 24, and 48 h. Samples subjected to sterile water treatment rather than the NaCl and NaHCO 3 -NaOH solution were used as negative controls [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the cold treatment, calli at same growth stage and condition were transferred at 4 °C and then collected within 0, 1, 6, 12, 24, and 48 h. Calli incubated at 25 °C were collected and used as negative controls [ 26 ]. For the salinity treatment, callus tissues were subjected to a 150 mM NaCl and NaHCO 3 -NaOH solution (pH 9.5) for 0, 1, 6, 12, 24, and 48 h. Samples subjected to sterile water treatment rather than the NaCl and NaHCO 3 -NaOH solution were used as negative controls [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Prior to this, the need for four CNGC subunits to combine to make a channel had been assumed by analogy with animal and bacterial channels, then supported by molecular modelling [ 78 ] (see Section 4 on channel structure). The range of subunit interactions found to date shows that they are not limited to co-members of the five phylogenetic groups within the family (I, II, III, IV-A and IV-B; Figure 1 [ 16 , 17 , 18 , 19 , 21 , 22 , 23 , 79 ]) but can occur across groups. Therefore, CNGC–CNGC interactions are isoform specific but are not restricted to closely related CNGC isoforms.…”
Section: Heteromeric Channel Complexes Also Occur In Plantsmentioning
confidence: 99%
“…CNGC promotors have been found to contain elements associated with responses to abscisic acid, auxin, ethylene, gibberellin, salicylic acid and methyl-jasmonate [ 17 , 18 , 19 , 20 , 21 ], and CNGC transcript levels are highly sensitive to abiotic and biotic stressors [ 17 , 18 , 19 , 20 , 22 , 23 , 79 ]. Notably, it has also been found that Ziziphus jujube CNGC2 expression is rapidly induced by application of cAMP to callus [ 79 ], potentially providing a mechanism for priming signalling pathways involving ZjCNGC2. In silico analysis has also predicted that NtabCNGC expression may be regulated extensively by micro-RNAs and cis -acting regulatory elements [ 18 ].…”
Section: Complex Formation Would Depend On the Co-localisation Andmentioning
confidence: 99%
“…Additionally, CNGC family has been characterized in Chinese jujube (Ziziphus jujuba Mill.) , and ZjCNGC2 was reported to regulate signaling cascades in response to cold stress ( Wang et al, 2020b ). Further, it was shown that rice CNGC14 and CNGC16 are involved in promoting tolerance toward heat and chilling stresses, and are regulators of Ca 2+ signals in response to temperature stress ( Cui et al, 2020 ).…”
Section: Calcium Sensing Network Under Cold Stressmentioning
confidence: 99%